Shear-promoted graphite-to-diamond phase transition at the grain boundary of nanocrystalline graphite - Dezhou Guo; Kun Luo; Qi An (Functional Diamond, 2024)
High pressure has traditionally been considered essential for the transformation of graphite into diamond. However, reducing the transition pressure required for this graphite-to-diamond (G2D) conversion holds significant appeal in both scientific research and engineering applications. In this study, we conducted large-scale molecular dynamics (MD) simulations using an environment-dependent interaction potential (EDIP) to examine the shear deformation of nanocrystalline graphite (n-graphite) with a grain size of approximately 6.5 nm. We discovered that the G2D transition pressure in n-graphite can be reduced to 2–3 GPa, significantly lower than the ∼90 GPa uniaxial stress required in crystalline graphite. This reduction is primarily due to concentrated local shear stresses at grain boundaries (GBs), which induce substantial rotations of graphite layers. These rotations facilitate the initial formation of diamond bonds at sites of pre-existing imperfections at the GBs, assisted by shear. Once initiated at the GBs, the G2D transition rapidly propagates within grains aligned parallel to the shear components, resulting in the formation of nanocrystalline diamond. Our findings underscore the critical roles of GBs and shear stress in enabling the G2D transition in n-graphite.